Family Conflict Resolution Based on Lampung Customary Local Wisdom and Its Implications for Household Harmony - Gandhi Liyorba Indra; Fathul Mu’in (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article examines family conflicts and their resolution based on the local wisdom of Lampung customs, including Pepadun and Saibatin. Because every household is always faced with conflicts, whether mild, moderate or severe, which can lead to household breakdown and social harmonization. Communities that still apply customary values in conflict resolution include Tanggamus and Way Kanan districts. The method used is qualitative, the type of research includes field research conducted in the indigenous Lampung Saibatin community in Tanggamus and Pepadun in Way Kanan. The approach used is ethnography and mubādalah approach. Primary data sources were obtained from Lampung traditional leaders in the two regions. This research found that conflict resolution is based on local wisdom by upholding the philosophy of life piil pesenggiri which priorities deliberation mechanisms, extended family support and conflict resolution offers. Lampung traditional local wisdom is in line with the principle of mubādalah because it provides guidance for family members in carrying out their roles by cooperating with each other, respecting each other and sharing roles for the welfare of the family that contributes to household harmony and divorce prevention.